Distribution of Foraminiferida South of Sherbrooke, Nova Scotia - Hooper, Kenneth (Atlantic Geology)

(untitled) (Maritime Sediments Editorial Board, 1978)
Bottom sediment samples (depths to 25m) from St. Mary's River, Gegogan, Wine Bay, Indian and Holland's Harbours, Nova Scotia, identified for the Foraminiferida by Habbishaw in 1970, were factor-vector analyzed. Based on 'total' populations 4 benthonia foraminiferal assemblages, not strictly biocenoses, are recognized. Assemblage I, dominated by Miliammina fusca, has a mean diversity of 4.75, a mean depth of 1.85 m, a mean pH (substrate) of 6.7, and the substrate is coarsegrained. This assemblage is found in the Upper Estuarine (intertidal) Zone in St. Mary's River, south of Sherbrooke. Assemblage 2, dominated by Eggerella advena, has a mean diversity of 12.5, a mean depth of 7 m, a mean pH (substrate) of 8.16, and the substrate is very fine-grained. It is found in the Lover Estuarine Zone in the lower reaches of St. Mary's River, Wine Harbour Bay, the western and northern areas of Gegogan Harbour, and the eastern shore south of Port Bickerton. Assemblage 3, dominated by Elphidium clavatum, has a mean diversity of 14.3, a mean depth of 9m, a mean pH (substrate) of 7.2, and the substrate is coarse- to fine-grained sand. It occurs in the Marginal Marine Zone (Scott) or Nearshore Biofacies (Bartlett) in St. Mary's River (3 to 5 km from the mouth) and at the head and near the mouth of Indian Harbour. Assemblage 4 dominated by Cibicides lobatulus, Eggerella advena and Elphidium clavatum, has a mean diversity of 19.9, a mean depth of 12.2m, a mean pH (substrate) of 7,16, and the substrate is medium- to fine-grained sand. It occurs in the Open Ocean-Nearshore Zone (Scott) or the Open Bay Biofacies (Bartlett), inside and outside Holland's Harbour, the southwest and central area of Indian Harbour, at the mouth of St. Mary's River, on the eastern side of Gegogan Harbour, and east of Crook Point.